2007
DOI: 10.1109/tcsi.2007.907845
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Circuit Design and Analysis for Database Search Applications

Abstract: In this paper, we show how quantum Boolean circuits can be used to implement the oracle and the inversion-about-average function in Grover's search algorithm. Before illustrating how this can be done, we present the circuit design principle using the satisfiability (SAT) problem as an example. Then, based on this principle, we show the quantum circuits for two different kinds of applications. The first one is searching a phone book. Although this is a typical example of Grover's algorithm, we show that it is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…We found some general techniques that can reduce the circuit size, although they have some side effects. For example, we can reduce the circuit by encoding the patent as a 3-SAT problem and then designing a quantum circuit from the 3-SAT problem 43 . For example, if we have three search items , we can use multiple MCX gates to mark the search items, as shown in Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We found some general techniques that can reduce the circuit size, although they have some side effects. For example, we can reduce the circuit by encoding the patent as a 3-SAT problem and then designing a quantum circuit from the 3-SAT problem 43 . For example, if we have three search items , we can use multiple MCX gates to mark the search items, as shown in Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Step [7], and a deletion when 1 . In particular, when 1 3 , the deletion is optimal since it is made with certainty for high data size [4].…”
Section: Basics On Quantum Computingmentioning
confidence: 99%
“…Searching items with respect to specific oracle were proposed by I.Y.L. Ju et al [7], they showed a circuit based implementation of the Grover's algorithm used for the database search process; but data basic operations like INSERT and DELETE have not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The SELECT query was deeply treated by Ju et al, 2 where they suggested a detailed CNOT-based circuit design that realizes the Grover's algorithm. Hu et al 3 proposed how to digitize the database itself to treat the search queries as a sequence of calls to factorized quantum search algorithm.…”
Section: Introductionmentioning
confidence: 99%